Simulations of the Water Food Energy Nexus for policy driven intervention. Issue 8 (August 2020) - Teitelbaum, Y.; Yakirevich, A.; Gross, A.; Sorek, S.
Abstract: Water-Food-Energy (WFE) resources exert mutual influences upon each other and thus cannot be managed separately. Information on household WFE expenditures addresses knowledge that distinguishes between geospatial districts' social welfare. Social welfare and investment in districts' WFE resources are interconnected. District (node) product of WFE normalized expenditures (Volume) is considered as a representative WFE Nexus holistic quantity. This Volume is assumed to be a function of residents' knowledge of welfare level across districts. We prove that the Volume rate conforms to Boltzmann entropy, and this is the premise of our hypothesis for directed information from high to low welfare between network nodes. Welfare mass (WM) represents the district's Volume combined with its income and population density. This WM is used as input into a model balancing between all domain nodes that allows policymakers to simulate the effects of potential quantifiable policy decisions targeted to individual districts at a domain level while also considering influences between districts. Based on existing historic data, the established tool exemplifies its potential by providing outcomes for Israel districts showing the influence of imposing different temporal allocation/deallocation actions as managerial regulations to prescribed districts. It is found that districts with a high WM do not suffer when a defund is applied, but districts that have a low WM gain from subsidies. Abstract : Finite Element Methods; Computational Fluid Dynamics; Wave Physics; Mathematical physics; Sustainable Development; Contaminant Transport; Environmental Risk Assessment; Groundwater; Water-Food-Energy (WFE) Nexus; Decision Support Systems (DSS); Integrated Water Resource Management and Policy (IWRMP).